Dermatoscopy of flat pigmented facial lesions-evolution of lentigo maligna diagnostic criteria - Miguel Costa-Silva; Ana Calistru; Ana Margarida Barros; Sofia Lopes; Mariana Esteves; Filomena Azevedo (Mattioli1885, 2018)
Recognition of facial lentigo maligna (LM) is often difficult, particularly at early stages. Algorithms and multivariate diagnostic models have recently been elaborated on the attempt to improve the diagnostic accuracy. We conducted a cross-sectional and retrospective study to evaluate dermatoscopic criteria aiding in diagnosis of flat pigmented facial lesions (FPFL). We examined 46 FPFL in 42 Caucasian patients and found that 4 of 20 dermatoscopic criteria reached the significance level required for features indicating malignancy namely, hyperpigmented follicular openings, obliterated follicular opening, annular-granular structures, and pigment rhomboids. Concomitant presence of at least 2 or 3 of the 4 mentioned criteria was significantly more frequent in LM than in pigmented actinic keratosis (PAK). However, despite more frequently seen in LM, these features were also displayed in some of the PAK and other FPFL, so we found them not specific for LM. Although dermatoscopy enhances the diagnostic accuracy in evaluating FPFL, histopathology remains the gold standard for correct diagnosis, making evident the need for improvements in early noninvasive diagnosis of LM.